Tracking adverse drug reactions and medication errors in the Central Chronic Medicine Dispensing and Distribution (CCMDD) programme in South Africa - Kennedy Otwombe; Maggie Munsamy; Mukesh Dheda; Nishana Ramdas; Corlee Herbst; Merlin Pillay; Tanya van Tonder; Celicia Serenata; Samanta Lalla-Edward (AOSIS, 2022)
Background: The South African Central Chronic Medicine Dispensing and Distribution (CCMDD) programme is a National Health Insurance (NHI) initiative that improves access to medicine for patients. Objectives: To describe the frequency of adverse drug reactions (ADRs) and medication errors reported in stable patients living with HIV. Method: This descriptive cross-sectional survey was conducted from August 2020 to October 2020, targeting tenofovir disoproxil fumarate/lamivudine/dolutegravir (TLD) and tenofovir disoproxil fumarate/emtricitabine/efavirenz (TEE) patients. The distribution of ADRs and medication errors is presented. Results: Of 9621 patients, 30.8% (n = 2967) were interviewed, 40.2% (n = 1192) on TLD and 59.8% (n = 1775) on TEE regimens. The majority were women (TLD: 55.8%, n = 665; TEE: 75.4%, n = 1338); 15% (179/1192) reported ADRs on TLD. Medication errors were low on TLD (1.6%, n = 19) and TEE (1.2%, n = 22). Receipt of incorrect medication (eight each in TLD and TEE) and associated hospitalisations (one vs two, respectively) were low. Common TLD-associated ADRs were weight gain (47.5%, n = 85), headaches (44.7%, n = 80), insomnia (39.7%, n = 71), restlessness (36.9%, n = 66), dizziness (29.6%, n = 53), brain fog (27.9%, n = 50), nervousness (27.4%, n = 49), rash on the skin (24.6%, n = 44) and poor concentration (21.2%, n = 38). Conclusion: About one in seven patients reported ADRs under TLD. Medication errors were low, possibly due to effective quality control measures and stable patients being on the programme. Knowing the frequency of ADRs and medication errors is critical for enhancing the CCMDD programme.